Investigating a new Dillenia ovata endophytic bacteria to produce antioxidants and anti-diabetes activity in vitro and in vivo - Linh Chi Tran; Chong Kim Thien Duc; Tuan Trong Nguyen; Duy Toan Pham; Danh Thai Luu; Trang Thi Xuan Dai (Biotechnology Reports)
A novel endophytic bacterium, Bacillus sp. DO-R5, with strong antioxidant and anti-diabetic properties, was isolated from Dillenia ovata, a traditional Vietnamese medicinal plant. Bacillus sp. DO-R5 was identified using morphological characteristics, SEM, and 16S rRNA sequencing, demonstrated the highest bioactivity among the 19 isolates. Optimal fermentation conditions (8.9 g/L D-glucose, pH 7.5, 38 °C, and 70.5 h) were determined using the Box-Behnken design. Under these conditions, Bacillus sp. DO-R5 significantly enhanced the production of bioactive compounds including diosmin, rutin, and chlorogenic acid, and exhibited improved in vitro antioxidant, anti-inflammatory, and anti-diabetic activities. In vivo, the extract effectively reduced blood glucose, regulated lipid profiles, supported weight control, and protected organs. These findings emphasize the potential therapeutic use of D. ovata endophytic bacteria as a natural source of anti-diabetic drugs.